PERAN PENDIDIKAN ISLAM DALAM MENINGKATKAN NILAI2 SPIRITUAL BAGI MAHASISWA PBA UNIVERSITAS ISLAM MALANG - Nur Hasan (Prodi Pendidikan Bahasa Arab Fakultas Agama Islam, 2021)
The study aims to identify the role of Islamic education in developing moral values among students of the Department of Arabic Language Education at the Indonesian Islamic University of Malang. To achieve this study, the researcher designed a tool to measure the role of Islamic education in promoting moral values for university students who must have the qualities of honesty, constancy, self-confidence, and honesty. and mastering their religious knowledge to enhance their moral values. The reality of Islamic education at the Indonesian Islamic University of Malang may significantly affect the formation of moral behavior among students, especially in the Arabic language teaching department, and in terms of objectives, it has certain characteristics, which is to train students to understand Islamic religious sciences on the approach of the Sunnis and the renaissance group, and to train them with characteristics Tolerance, balance, justice, and these qualities are a mission of the Nahdlatul Ulama Society, which is the largest Islamic society in Indonesia. The study recommended the development of a strategic plan that enables the Ministry, educational institutions and designated associations to develop the Islamic education curriculum in such a way that it adopts their Islamic religious knowledge and avoids students from the characteristics of religious extremism, inculcates moral values and strengthens them using organized religious educational methods and educates them in good behavior during their studies at the university. And addressing wrong behaviors according to their importance.Â Key words: The role of Islamic education, development of moral values, Students of the Department of Arabic Language Teaching.